KRITIK TERHADAP TEORI AKUNTANSI POSITIF - Salampessy, Zulkarim (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Theory is a set of principles of hypothesis, conceptual and pragmatic, which is connected to one another, forming a frame of reference for an area of knowledge. Accounting theory is defined as a logical reasoning in the form of a set of principles or the principles that (1) is a frame of reference to assess the accounting practices and (2) guidelines for the development of practices and procedures are new. normative accounting theory (prescription) is a statement or proposition that requires or require accountants in accounting practices. Positive accounting theory (description) aims to explain and predict accounting practice. Main problem is that current accounting practices and management attitudes towards such practices. Positive accounting theory realist ontology adopted a strong understanding and this determines epistemology and methodology. Methodologically, this is a positivist or modernism, it is committed to using methods of physics. As a result of this is rooted in empirical epistemology. Positive accounting theory bersandarkan utility maximization which has a central assumption of neo-classical ie, each individual has a goal to pursue personal interests. Thus there are several things that need to be done or that the theory should be developed to overcome the weakness of positive accounting theory. Not the goal to replace the existing positive theories, but to complement the existing deficiencies in order to improve the positive accounting theory in order to provide meaningful value. Proposed alternatives are: Integrated Utility, Value Free to Value Laden, S-Matrix Theory, Extention Maximation. Keywords: Theory of Accounting, Accounting Theory Normative, Positive accounting theory